The Lioness Roared - Beem, C. author. aut Link
VIII, 272 p.
Keywords: Charles Beem uses Gender Studies and political and constitutional History to examine the problems faced by female rulers throughout British history, from the twelfth century Empress Matilda's imaginative efforts to become England's first regnant queen, to Queen Victoria's remarkable exercise of political power during the Bedchamber Crisis of 1839.